Experimental and Numerical Study on Dynamic Response of High-Pier Ballastless Continuous Beam Bridge in Mountainous Area - Wenshuo Liu; Qiong Luo; Gonglian Dai; Xin Tang (Applied Sciences)
The dynamic performance of a ballastless track on bridges affects the vibration performance of the vehicle–bridge coupling system, which, in turn, will affect safety, the smoothness of operating trains, and passenger comfort. However, in the existing literature, few studies focus on the coupled vibration response analysis of large-span continuous beam bridges for high-speed railways, especially high-pier bridges. Dynamic response tests with multiple measurement points installed on the rail, concrete slab, and bridge deck are conducted. This study investigates the dynamic characteristics of bridges with high piers under train loads. A dynamic system is built by the co-simulation platform of SIMPACK v9 and ANSYS v2022, consisting of several models, a coupling mechanism, etc. The vibration response of a train passing through the bridge at 300 km/h is analyzed, and the influence of operating speed on the motivation performance of the coupled system is further studied. The results indicate that the simulation results are validated against experimental data, showing good agreement; the train–track–continuous beam bridge coupling system meets the specification limits and has some margins for further optimization with an operating speed of 300 km/h. The refined model of train–rail–bridge coupling vibration established in this paper provides theoretical guidance for the design and application of high-speed railways.